Exploring secular trends and types of tuberculosis burden in India over past three decades through insights from the Global Burden of Disease Study 2019 - Krittika Bhattacharyya; Ravi Prakash Jha; Deepak Dhamnetiya; Priyanka Patel; Neha Shri; Mayank Singh (Discover Public Health)
Abstract Objective This study evaluates the trends in tuberculosis (TB) incidence, prevalence, mortality, and disability-adjusted life years (DALYs) in India over a 30-year period, from 1990 to 2019. Data and methods This study leverages data from the Global Burden of Disease Study 2019. We employed Joinpoint regression analysis to determine the average annual percent changes (AAPCs) and their corresponding confidence intervals for age-standardized rates. Result Our findings reveal a significant reduction in the overall TB burden, with incidence declining from 390.22 to 223.01, prevalence from 707.94 to 390.03, mortality decreasing from 121.72 to 36.11 per 100,000, and DALYs reducing at an average annual rate of 4.01%. In stark contrast, multidrug-resistant TB (MDR-TB) exhibited substantial increases across all indicators, with an AAPC of 14.27% for incidence, 14.05% for prevalence, 11.06% for mortality, and 11.16% for DALYs. Conclusion Our findings indicate that TB metrics consistently remain higher among males compared to females across all subtypes. The ongoing increase in multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB), coupled with the growing threat of antimicrobial resistance (AMR), underscores the urgent need for advancements in diagnostic capabilities, broader access to effective treatment, and enhanced public health awareness. AMR complicates TB management by limiting the efficacy of existing drugs, making it even more critical to address resistant strains with innovative solutions. Joint modeling efforts for TB and AMR are necessary to better understand their interactions, predict future trends, and develop integrated strategies for effective control. To achieve the ambitious target of eliminating TB by 2025, as set by India's National Tuberculosis Elimination Programme, such intensified and focused efforts are crucial. Strengthening early detection, optimizing treatment strategies, and raising community awareness will be essential to curb the spread and impact of resistant TB forms, while mitigating the broader implications of AMR.